Ruthenium-Catalyzed Cross-Selective Asymmetric Oxidative Coupling of Arenols - Hayashi, Hiroki; Ueno, Takamasa; Kim, Chungsik; Uchida, Tatsuya (Organic letters, 2020)
(Aqua)ruthenium(salen) complex 1c achieved good to high chemo- and enantioselective oxidative cross-coupling of arenols. The catalytic system can be used to selectively produce C 1-symmetric bis(arenol)s from the combination of C3- and C7-substituted 2-naphthols or phenols even when there is no significant difference in oxidation potential between the cross-coupling partners. This unique cross-selectivity is dominated by steric rather than electronic effects of the arenols and can be controlled by chemoselective single-electron oxidation and oxidative carbon–carbon bond formation.